- #1

- 84

- 0

t-=2∏[itex]\sqrt{(l/g)}[/itex] or t=2∏[itex]\sqrt{(1/T/m)}[/itex] ; l=length of the pendulum

T=time period of the pendulum

m=mass of bob

Note:g is not equal to T/m as there is pseudo centrifugal force such that T + centripetal force=mg

- Thread starter anigeo
- Start date

- #1

- 84

- 0

t-=2∏[itex]\sqrt{(l/g)}[/itex] or t=2∏[itex]\sqrt{(1/T/m)}[/itex] ; l=length of the pendulum

T=time period of the pendulum

m=mass of bob

Note:g is not equal to T/m as there is pseudo centrifugal force such that T + centripetal force=mg

- #2

- 263

- 0

The first one is the useful expression...

- Replies
- 4

- Views
- 7K

- Last Post

- Replies
- 3

- Views
- 3K

- Replies
- 23

- Views
- 20K

- Replies
- 11

- Views
- 2K

- Last Post

- Replies
- 10

- Views
- 5K

- Replies
- 2

- Views
- 606

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 6

- Views
- 3K

- Last Post

- Replies
- 2

- Views
- 2K